PELAYANAN SURAT IZIN MENGEMUDI (SIM) OLEH POLRESTA PEKANBARU (STUDI KASUS SIM KELILING) - Sari, Wully Hilma; Tua RFS, Harapan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
In the era of globalization and reformation, one of the farm of services needed by the community is the service can provide convenence to get the service quickly, easily, and safely. Therefore, Polresta Pekanbaru makes facility to get driving license or SIM more easily, fastly and comfortably by using the mobile SIM car.In this study, the researcher wants to know how the service extention of a driver’s license that provided by Polresta Pekanbaru. The aim of this research are to know and describe about the service of SIM car in Pekanbaru. This research uses Widodo theory, (2001: 270-271), that is: (1) service procedures, (2) completion time, (3) service charge, (4) product service, (5) facilities and infrastructure, and (6) competence officer. The research uses qualitative descriptive approach, data collection technique is by interview, observation and documentation. The informant in this research is one of the head of unit reg ident, one part of the reg ident, and some people. The results of this research are one of the procedure is very easy and fast, understanding and implementation has been running well which is the applicants have no trouble in the management of the driver’s license. The resolution time is considered very quickly which is about 10-15 minutes. As for the cost that is in accordance with the Non Tax State Revenue (PNBP). The product service and competence of police officers ready considered good enough, but only in terms of facilities and infrastructure are still inadequate. The factors that affect the driver’s license in the city of pekanbaru, namely: often in internet network, still a lack of socialization the pekanbaru police to the public against the schedule and the driver’s license around, as well as less friendly officers in providing services to the community.Keywords: Public Services, Extention of Driver’s License, and Mobile SIM Car